2019
DOI: 10.1080/21691401.2019.1609979
|View full text |Cite
|
Sign up to set email alerts
|

Anagliptin protects neuronal cells against endogenous amyloid β (Aβ)-induced cytotoxicity and apoptosis

Abstract: Excessive generation and accumulation of amyloid-b (Ab) fragments by familial mutations of amyloid precursor protein (APP) and presenilin 1 (PS1) play a key role in causing oxidative stress, mitochondrial abnormalities and neuronal apoptosis in Alzheimer's disease (AD). Anagliptin, a novel DPP-4 inhibitor, is a clinical drug for the management of type II diabetes approved for use in 2012. Little on the pharmacological function of anagliptin against Ab-induced cytotoxicity in neuronal cells is known. Here, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…21,22 Recently, it was reported that the cytotoxicity and apoptosis induced by endogenous amyloid β in the neurons could be alleviated by anagliptin. 23 Pronounced antioxidative stress effects have also been reported during the treatment of type II diabetes with anagliptin. 24 In the present study, the protective effect of anagliptin against oxygen−glucose deprivation and reoxygenation (OGD/R)-induced injury on bEnd.3 brain endothelial cells will be investigated to explore the potential therapeutic property against CIRI.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 Recently, it was reported that the cytotoxicity and apoptosis induced by endogenous amyloid β in the neurons could be alleviated by anagliptin. 23 Pronounced antioxidative stress effects have also been reported during the treatment of type II diabetes with anagliptin. 24 In the present study, the protective effect of anagliptin against oxygen−glucose deprivation and reoxygenation (OGD/R)-induced injury on bEnd.3 brain endothelial cells will be investigated to explore the potential therapeutic property against CIRI.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The molecular structure of anagliptin is shown in Figure . Anagliptin has shown promising antidiabetic properties in both clinical trials and animal experiments. , Recently, it was reported that the cytotoxicity and apoptosis induced by endogenous amyloid β in the neurons could be alleviated by anagliptin . Pronounced antioxidative stress effects have also been reported during the treatment of type II diabetes with anagliptin .…”
Section: Introductionmentioning
confidence: 99%
“…17 Aβ oligomers can directly destroy the ion channels to enter the cell for aggregation and can also activate the intracellular signaling pathways by binding to a variety of receptors on the cell membrane surface, causing cell injuries such as lipid peroxidation, increase of reactive oxygen species (ROS), dysfunction of mitochondria, and inducing cell apoptosis. 18 Aβ 25-35 , the active fragment of a synthetic β amyloid protein, is similar to Aβ 1-42 in biological activities, and is commonly used to induce both in vitro and in vivo AD models. 19 In recent years, great progress has been made in the application of active components of traditional Chinese medicines in the treatment of AD, such as saponins, flavonoids, and polysaccharides.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study revealed that CASP3 is the most important enzyme in apoptosis, and when activated, A β can induce neuronal apoptosis [ 51 ]. In addition, two other studies showed that CASP3 mediates the cleavage of amyloid precursor protein (APP) to yield neurotoxic peptide fragments, which leads to an increase in production of beta-amyloid [ 52 , 53 ]. A previous study showed that VEGFA plays an important role in angiogenesis, which has a protective effect in people at high risk of AD [ 54 ].…”
Section: Discussionmentioning
confidence: 99%